Prevalence of irritable bowel syndrome(IBS)among healthy subjects using valida ted Bahasa Malaysia version of rome lll IBS questionnaire - Anuar, Waid (2008)
Irritable bowel syndrome (IBS) is a very common chronic gastrointestinal disorder characterized by recurrent abdominal pain and altered bowel habits without major organic disease. ROME diagnostic criteria, based on subjective gastrointestinal (GI) complaints are the most widely used criteria for diagnosing ffiS. We have developed Bahasa Malaysia version of ROME III IBS questionnaire for the study of ms in Malaysia. This validated questionnaire was used to study the prevalence of ms among healthy subjects. The aims of this study were, 1) to validate the Bahasa Malaysia version of ROME III IBS questionnaire and ROME III psychosocial alann questionnaire. 2) to determine the prevalence of IBS among normal healthy subjects in USM Health Campus, Kelantan using a validated Bahasa Malaysia version of ROME III ffiS questionnaire and ROME III psychosocial questionnaire This study was divided into two phases: I) the validation process of the proposed translated questionnaire and 2) a cross sectional prospective studies to examine the prevalence of IBS among healthy subjects in a university campus. The validated BM version of IBS ROME III questionnaire was shown to have good clinimetric properties. The prevalence of IDS among healthy subjects in USM Health Campus was 11.8%. Prevalence of ms was significantly associated with age, ethnicity and level of formal education. Redtlag and psychosocial alann symptoms were higher in subjects with ms. This validated Bahasa Malaysia version of ms ROME III questionnaire had good clinimetric properties suitable as a tool for research. Prevalence and characteristics of ms among healthy subjects in USM Healthy Campus was almost similar to those reported in other Asian population.